Young people's and professionals' views about ways to reduce teenage pregnancy rates: To agree or not agree. Issue 2 (1st April 2002) - Chambers, Ruth; Boath, Elizabeth; Chambers, Stephanie
Abstract : Context: We know little about young people's views of the effectiveness of interventions to reduce the frequency of teenage pregnancy. Objective: To compare the views of young people and professionals about ways to reduce the frequency of teenage pregnancy. Design: Comparison of consensus emerging from adult and teenagers' workshop discussions and subsequent modified two-round Delphi questionnaires for each subject group. Setting: North Staffordshire community. Participants: Fifty-six professionals from health, education, social care, youth and community and other sectors and 55 young people. Main outcome measures: Views with which at least 70% of participants agreed. Results: Young people emphasised the importance of interventions being young person-centred, whereas professionals stressed that re-organisation of sexual health and education services was key. Young people suggested more creative ways of communicating health and education messages than did professionals. Both groups advocated peer education and recognised the need for developing help and services for young men. Both suggested that staff should be educated to be more sensitive in relating to young people. Professionals and young people advocated the locating of sexual health services for teenagers in youth settings. Conclusion: In the main, professionals favoured dedicated young people's services whilst young people emphasised the need for young person-centred services. Those working in the health and education sectors should seek and listen to young people's views and preferences when planning and providing sexual health education and services.